Generation, characterization and application of atmospheric pressure plasma jet - Shrestha, R.; Subedi, D.P.; Gurung, J.P.; C., S. Wong (Penerbit Universiti Kebangsaan Malaysia, 2016)
The development of a non-thermal plasma jet with a capillary configuration working at atmospheric pressure is reported in this paper. The plasma jet is powered by a power source with frequency of several kilohertz. The working gas is argon. The plasma obtained has been characterized by optical emission spectroscopic measurements and electrical measurements of the discharge using voltage and current probes. The electron temperature has been estimated by using the modified Boltzmann plot method utilizing the Ar 4p-4s transition. The electron temperatures at various positions along the plasma jet length have been obtained and it is found that the electron temperature decreases at position further from orifice. The electron density has been estimated from current and voltage measurements using the power balance method. The effects of gas flow rate, applied voltage and frequency on the characteristics of the plasma jet have also been investigated. The applications of the atmospheric pressure plasma jet (APPJ) developed to modify the surface properties of Polyethyleneterephthalate (PET) and polycarbonate (PC) have been tested. Our results showed that the atmospheric pressure non-thermal plasma jet can be effectively used to enhance the surface wettability and surface energy of the PET and PC. The plasma jet has also been tested for inactivation of prokaryotic cells (Escherichia coli, Staphylococcus aureus). In the case of E. coli, better than 4 log10 reduction can be achieved. The effect of plasma jet on the pH of cell culture medium has suggested that the plasma species, particularly the electrons, are solely responsible for the effect of inactivation of living cells.